Preparation of poly (styrene‐co‐allyl sulfonic acid) as a novel catalyst for the alcoholysis of dioscin. (12th March 2020) - Yuan, Hui; Yu, Xuejun; Shen, Bowei; Zhang, Farong; Jiang, Wenxiu; Pan, Zhiquan; Zhou, Hong
Abstract : This work describes the preparation of a novel solid acid, poly (styrene‐co‐allyl sulfonic acid) (St‐SAA), and its activity test for extracting diosgenin from Dioscorea Zingiberensis C.H. Wright (DZW). The solid acid was synthesized by the radical polymerization of styrene and sodium allyl sulfonate in water/ethanol solution, followed by the acidification. The prepared solid acid was characterized by infrared spectrum (FTIR), thermogravimetric analysis (TGA), X‐ray photoelectron spectroscopy (XPS), element analysis, and scanning electron microscope. The solid acid catalyst was used to extract diosgenin from DZW. It was found that the alcoholysis activity of the solid acid was higher than the hydrolysis activity of sulfuric acid with the same mass under the same conditions. Besides, the solid acid can be separated from the reaction mixture for the recycling extraction of diosgenin, and the solid acid has no loss of mass and no decrease of alcoholysis activity after repeated cycles.